Go Green : Waste Management - Om Books International (Om Books International, 2019)
What happens to the garbage that we throw every day? Where is it dumped? Why is it necessary to dispose the garbage safely? Is all garbage waste, or can it be reused? This vividly illustrated, delightful and extremely informative book answers all your queries and makes you aware of the importance of waste management.
Keywords: Sharing The Planet -- -Waste Management